ANALISIS LITERASI MATEMATIK PESERTA DIDIK DITINJAU DARI TIPE KEPRIBADIAN HIPPOCRATES-GALENUS: TIPE SANGUINIS - Farida Hendriani; Nani Ratnaningsih; Nurfadilah Siregar (Gema Pendidikan, 2021)
This study analyses students' mathematical literacy in terms of the Hippocrates-Galenus Personality Type, which focuses on the Sanguinist Type; This study uses a qualitative descriptive method with an exploratory approach. The subjects of this study were four grade, six students. The research subjects were taken based on each personality type's most dominant personality type and had the highest mathematical literacy. Data collection techniques used a Hippocrates-Galenus personality type questionnaire, mathematical literacy tests, and unstructured interviews. The Hippocrates-Galenus Personality Type questionnaire results show that five students have the sanguine type characteristics; there are two choleric types, three melancholy types, and seven phlegmatic types.